Immunological Detection of Avian Influenza Virus in Infected Ducks by Monoclonal Antibodies Against AIV-H5N1 - NYOMAN MANTIK ASTAWA; IDA BAGUS OKA WINAYA; LUH PUTU AGUSTINI; NINING HARTANINGSIH (Microbiology Indonesia, 2007)
In order to establish a detection method for avian influenza virus (AIV) infection in ducks, monoclonal antibodies (MAbs) against the virus were produced. The virus used for the production of the monoclonal antibodies was AIV-H5N1 of Indonesian origin. Immortal mouse myeloma were fused with the lymphocytes derived from the spleen of mice immunized with the virus. The MAbs were tested for their specificity by enzyme linked immunosorbent assay (ELISA) and western blotting using formaldehyde inactivated virus and normal allantoic fluid as a negative control. Twelve MAbs which were specific against AIV were isolated and 8 of them were used for detecting of AIV antigen in duck’s tissues. AIV antigen was detected in paraffin embedded tissues of AIV-infected ducks by immunohistochemistry using MAbs. AIV antigen was not detected in ducks, which were confirmed to be AIV negative. In the infected ducks, high intensity of AIV infection was detected in proventricle gland and small intestine. The AIV antigen with a lesser intensity was also detected in lungs, spleen, and bursa of Fabricius, but hardly detected in muscle, brain, and several other issues. This study shows a clear evidence that MAbs produced in this study are applicable for use in immunological detection of AIV in infected duck tissues.